USING 3D MODELS FROM MULTIDETECTOR COMPUTED TOMOGRAPHY IMAGES FOR DIAGNOSTIC OF HALLUX-VALGUS - Catal, Hatice; Corumluoglu, Ozsen (STEF92 TECHNOLOGY LTD, 2012)
Medical image processing techniques is often used in medicine or some engineering fields. In this study, we used basic techniques of metric digital image processing. Axial MDCT (Multidetector Computed Tomography) Ballerina's feet images were used to form 3D models by 3D-Doctor software. The virtual 3D models are in high accuracy. Hallux-valgus angles were calculated and recorded by using these 3D virtual models. We hope that the results from the biometric and reconstructive techniques carried out in this work will contribute to the present knowledge in medicine especially on ballerina's foot health and digital image processing in this area.
Keywords: Hallux-valgus; Medical Photogrammetry; 3D; MDCT; Digital Image Processing; Geology; Mining & Mineral Processing